Estimates of genetic and phenotypic parameters of some reproductive traits of African common goats in Rwanda - Mourad, M. (Elsevier, 1994)
Records of 2239 African Common does were collected in the French project in Masaka-Kigali during 1989 to 1992. All does were artificially inseminated with semen from selected Alpine bucks from France. Age of does affected significantly (P